Copépodes (Crustacea, Calanoida, Cyclopoida) planctônicos em reservatórios profundos e dendríticos: efeitos do tempo de residência e da idade de formação - Perbiche-neves, Gilmar (2014)
Some ecological attributes of planktonic copepods (composition, diversity, abundance and its relations with limnological variables) were compared in two deep and dendritic reservoirs, 470km from each other, with contrasting water retention time (WRT) and ages of construction. Data were grouped from two different studies: samples were collected monthly between March/00 to February/01, on the Salto Caxias Reservoir (Iguaçu River), and tri-monthly between January/00 to October/01, on the Chavantes Reservoir (Paranapanema River). Eight species of Calanoida and six of Cyclopoida were identified in both reservoirs. The highest richness was observed in Salto Caxias (12 taxa) when compared with Chavantes (8 taxa), and six species were exclusive to Salto Caxias and two from Chavantes. Salto Caxias was studied one year after the construction, consequently with higher nutrients values in this period and showed generally high mean values of Copepoda (nauplius, copepodits and adults) than Chavantes, which is 38 years old. Some parameters as transparency, conductivity, turbidity and total nitrogen were significantly related with copepod abundance. New formation and sufficient long WRT could be an important cause for the highest richness of Calanoida and total abundance of individuals in Salto Caxias Reservoir.